Inter-individual variability in LDL-C reductions with inclisiran – data from ORION-10 and ORION-11. (25th November 2020) - Wright, R.S; Raal, F.J; Kallend, D; Stoekenbroek, R; Koenig, W; Leiter, L.A; Landmesser, U; Schwartz, G.G; Wijngaard, P.L.J; Kastelein, J.J.P; Ray, K.K
Abstract: Introduction: Inclisiran, an investigational siRNA, has been shown to effectively and durably lower LDL-C in Phase 3 trials. Inter-individual variability in LDL-C reductions has been documented for statin therapy and ezetimibe. Purpose: To evaluate the inter-individual variability in LDL-C lowering with inclisiran. Methods: The Phase 3 ORION-10 and ORION-11 trials randomized patients with established ASCVD (or risk-equivalents) who had LDL-C >70 mg/dl despite maximally tolerated statins to inclisiran or placebo (1:1). Inclisiran sodium 300 mg was administered s.c. at baseline, three months later, then every six months. Co-primary endpoints were the LDL-C reduction from baseline to Day 510 and the time adjusted average % change in LDL-C reduction after Day 90 and up to Day 540. Measures of response variability were pre-specified secondary endpoints. This analysis examines the inter-individual variability of LDL-C reductions at day 510 using pooled data from both trials. Results: The analysis included 3178 individuals (92% on statins). At Day 90, 97% of inclisiran-treated patients had an LDL-C reduction. At Day 510, the median percent reduction in LDL-C levels from baseline was 57.3% in the inclisiran group (interquartile range, 44%-70%). An LDL-C reduction ≥50% was reached by 1359 (86.6%) inclisiran-treated patients versus 97 (6.2%) placebo patients at any visit (odds ratio [OR] 97.6, 95% confidence interval [CI] 76–126). An LDL-C reduction ≥30% was reached by 1523 (97.0%) inclisiran-treated patients versus 371 (23.7%) placebo patients (OR 104.5, 95% CI 76–143). At Day 510, 921 patients (65.1%) in the inclisiran group had a reduction ≥50% in LDL-C compared to 34 patients (2.4%) in the placebo group, and 1228 (86.8%) had a reduction ≥30% compared to 148 (10.5%), respectively. Among placebo-treated patients, there was a substantial proportion with notable increases in LDL-C at Day 510 (figure). Conclusion: In Phase 3 trials, inclisiran on top of maximally tolerated statins provided reliable, consistent and durable reductions in LDL-C. A large percentage of subjects randomized to inclisiran achieved substantial reductions (>50%) in LDL-C and nearly all achieved at least a 30% reduction suggesting inclisiran is potentially a promising novel therapy for patients needing sustained LDL-C reductions. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): The Medicines Company